Myoepithelioma of soft tissue - Pai Mukhta; Naik Ramadas; Kamath Ramachandra; Magar Dilasma (Wolters Kluwer Medknow Publications, 2009)
Myoepitheliomas and mixed tumors involving deep subcutaneous and subfascial soft tissues of limb or limb girdle are rare lesions as against salivary lesions that are well established conditions. Here, we report a 22-year-old female who presented with painful hard swelling in the left gluteal region of 1½ year duration. MRI showed a large ill-defined heterogeneous mass lesion measuring about 7-8 cm. in the left sacral region eroding the left sacroiliac region and left sacroiliac joint. With a clinical diagnosis of chondrosarcoma, the tumor with the surrounding tissue was resected in segments at surgery. Histomorphology revealed nests, sheets and cords of round to spindled cells with extensive squamous metaplasia in a myxoid to fibrous stroma. These cells extensively infiltrated muscle and bone. The tumor cells expressed immunoreactivity for cytokeratin (AE1/AE3) and S-100.